2020
DOI: 10.1007/s11356-020-07885-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of companion planting and PGPR for the assisted phytoextraction of trace metals (Zn, Pb, Cd)

Abstract: Biomass production and metal accumulation in plant tissue (bioconcentration) are two critical factors limiting the phytoextraction rate. Metal translocation to aboveground organs should be accounted for as the third most important factor, as harvesting of the plant roots is usually economically disadvantageous. These three parameters could be potentially increased with the use of companion planting, a well-known agricultural technique, and inoculation with plant growth–promoting bacteria (PGPB). The aim of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 95 publications
(113 reference statements)
0
31
0
1
Order By: Relevance
“…Abdollahi et al [ 38 ] research showed that inoculation of PGPR increased the phytoavailability of Cd and Pb and also improved the growth of cabbage varieties. Konkolewska et al [ 39 ] also documented that PGPR increased the rate of heavy metal phytoextraction mainly by increasing the production of dry biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Abdollahi et al [ 38 ] research showed that inoculation of PGPR increased the phytoavailability of Cd and Pb and also improved the growth of cabbage varieties. Konkolewska et al [ 39 ] also documented that PGPR increased the rate of heavy metal phytoextraction mainly by increasing the production of dry biomass.…”
Section: Discussionmentioning
confidence: 99%
“…With microbial assistance, metal extraction or stabilization efficiencies can be enhanced substantially. For instance, the PGPB Burkholderia phytofirmans inoculation enhanced the Brassica juncea phytoextraction efficiency of Zn, Cd and Pb by 37%, 21% and 10%, respectively (Konkolewska et al, 2020). Sunflower inoculated with Bacillus proteolyticus accumulated 40% less Cd and 20% less Pb in aboveground tissues, suggesting enhanced phytostabilization induced by PGPBs (Radziemska et al, 2020;Saran et al, 2020).…”
Section: Microbial-based Bioremediationmentioning
confidence: 97%
“…In this sense, it is worth highlighting the so-called Plant Growth Promoting Rhizobacteria (PGPR), highly efficient to increase plant growth and increase their tolerance to biotic and abiotic factors. This particular type of phytoremediation using PGPRs in combination with plants is called phytorhizoremediation [15]. The success of this technique lies in the fact that the rhizosphere is an interface in which plants and microorganisms establish complex and varied molecular relationships, which involve the nutrients transfer, as well as specific interactions mediated by the release of signaling molecules from plant roots [16].…”
Section: Introductionmentioning
confidence: 99%